Modulation of the Innate Immune Response by Human Neural Precursors Prevails over Oligodendrocyte Progenitor Remyelination to Rescue a Severe Model of Pelizaeus‐Merzbacher Disease. (31st December 2015) - Marteyn, Antoine; Sarrazin, Nadège; Yan, Jun; Bachelin, Corinne; Deboux, Cyrille; Santin, Mathieu D.; Gressens, Pierre; Zujovic, Violetta; Baron‐Van Evercooren, Anne
Abstract : Pelizaeus‐Merzbacher disease (PMD) results from an X‐linked misexpression of proteolipid protein 1 (PLP1). This leukodystrophy causes severe hypomyelination with progressive inflammation, leading to neurological dysfunctions and shortened life expectancy. While no cure exists for PMD, experimental cell‐based therapy in the dysmyelinated shiverer model suggested that human oligodendrocyte progenitor cells (hOPCs) or human neural precursor cells (hNPCs) are promising candidates to treat myelinopathies. However, the fate and restorative advantages of human NPCs/OPCs in a relevant model of PMD has not yet been addressed. Using a model of Plp1 overexpression, resulting in demyelination with progressive inflammation, we compared side‐by‐side the therapeutic benefits of intracerebrally grafted hNPCs and hOPCs. Our findings reveal equal integration of the donor cells within presumptive white matter tracks. While the onset of exogenous remyelination was earlier in hOPCs‐grafted mice than in hNPC‐grafted mice, extended lifespan occurred only in hNPCs‐grafted animals. This improved survival was correlated with reduced neuroinflammation (microglial and astrocytosis loads) and microglia polarization toward M2‐like phenotype followed by remyelination. Thus modulation of neuroinflammation combined with myelin restoration is crucial to prevent PMD pathology progression and ensure successful rescue of PMD mice. These findings should help to design novel therapeutic strategies combining immunomodulation and stem/progenitor cell‐based therapy for disorders associating hypomyelination with inflammation as observed in PMD. Stem Cells 2016;34:984–996